Biomarkers for occupational manganese exposure. (14th September 2022) - Karyakina, Nataliya A.; Shilnikova, Natalia; Farhat, Nawal; Ramoju, Siva; Cline, Brandon; Momoli, Franco; Mattison, Donald; Jensen, N.; Terrell, R.; Krewski, Daniel
Abstract: Long-term inhalation exposure to manganese (Mn) metal or its inorganic compounds can result in manganism or subclinical neurofunctional deficits. Studies have described affected workers in Mn dioxide mining, Mn-containing ore crushing and milling facilities, manufacturing of dry-cell batteries, Mn steel and alloy production plants, and in welders. The objective of this study was to critically review existing evidence on the reliability of potential biomarkers of Mn exposure, specifically the relationship between inhalation exposure to Mn particulates in different occupational settings and Mn concentrations in blood and other biological fluids and tissues, with a particular focus on whole blood as a potentially useful medium for measuring internal tissue dose. We also examined available evidence on the relationship between Mn levels in blood and adverse clinical and subclinical neurotoxic outcomes. Three bibliographic databases were searched for relevant studies and identified references were screened by two independent reviewers. Of the 6338 unique references identified, 76 articles were retained for data abstraction. Findings indicate that the relationships between Mn in blood and both external Mn exposure indices and neurofunctional impairments are limited and inconsistent. Different sources of exposure to Mn compounds, heterogeneity in the methodological approaches, and inadequate reporting of essential information limited direct comparison of the reported findings. Among the Mn-exposure biomarkers considered in this review – including biomarkers in blood, plasma, serum, erythrocytes, urine, bone, toenails, fingernails, hair, saliva – biomarkers in whole blood may provide to be most useful in Mn biomonitoring and risk assessment.